PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE FORMULATE-SHARE-LISTEN-CREATE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Sintia Kartika Sari (Departemen Matematika, 2020)
This research is a literature study. Through this research, we will describe theoretically the effect of the FSLC cooperative learning model on students’ understanding of mathematical concept. The data analysis technique used is content analysis. Based on the study conducted, it was found that theoretically the FSLC type cooperative learning model could have an effect in increasing students’ understanding of mathematical concept. This is because at each stage of the FSLC it helps students to be actively involved and construct their own understanding in increasing understanding of mathematical concepts. Formulate activities will support students to be able to think independently and be able to construct their own thinking result. Sharing activities will support students to gain new understanding from the results of discussions with their partners. Listen activities make students give direction and good understanding. The create activity will help students embed the concepts they learn. Keywords—Understanding of Mathematical Concepts, Formulate-Share-Listen-Create (FSLC) Cooperative Learning Model